Coin Iconography of Archangel St. Michael and its Political Symbolism in Western Europe during the Late Middle Age - de Francisco Olmos, José María (Eikón / Imago, 2012)
This paper reviews the importance of the iconography of Archangel St. Michael in coin mintages in the late Middle Ages. Beginning by its presence in the Byzantine coins in the eleventh century, we explain the reasons of the Archangel’s appearance in this Empire, and the importance of its sanctuaries and veneration in Occident. It did not appear on coins, however, until mid fourteenth century in France, in the French Valois dynasty at the beginning of The Hundred Years’ War, setting an important political impact. Not until the second half of the fifteenth century did this impact resume, at that moment in England, France and Naples the Archangel’s image dominated a few coinage series with a very similar iconography. The monarchs of those countries felt the need to justify their power and decided to use the divine endorsement which contributed to their victory over the rebellions organised by their nobility, drawing upon the analogy of the victory of the Archangel over the rebel demons that rose against God.